2020
DOI: 10.3390/plants9060699
|View full text |Cite
|
Sign up to set email alerts
|

Τhe Nematicidal Potential of Bioactive Streptomyces Strains Isolated from Greek Rhizosphere Soils Tested on Arabidopsis Plants of Varying Susceptibility to Meloidogyne spp.

Abstract: A total of 461 indigenous Streptomycetes strains recovered from various Greek rhizosphere habitats were tested for their bioactivity. All isolates were examined for their ability to suppress the growth of 12 specific target microorganisms. Twenty-six were found to exert antimicrobial activity and were screened for potential nematicidal action. S. monomycini ATHUBA 220, S. colombiensis ATHUBA 438, S. colombiensis ATHUBA 431, and S. youssoufensis ATHUBA 546 were proved to have a nematicidal effect and thus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…However, the majority of compounds, including grecocycline A, grecocycline B, ageloline A, phencomycin, strepoxazine A, strepthonium A, petrocidin A and SKC3, are novel compounds with no other known producers. Greek environments, such as rhizosplere soils, are both rich in streptomycetes and relatively unexplored, making them of great research interest [11]. Actinobacteria, which include Streptomyces, are dominant in arid environments [56], which explains why they are easily isolated from Greek soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of compounds, including grecocycline A, grecocycline B, ageloline A, phencomycin, strepoxazine A, strepthonium A, petrocidin A and SKC3, are novel compounds with no other known producers. Greek environments, such as rhizosplere soils, are both rich in streptomycetes and relatively unexplored, making them of great research interest [11]. Actinobacteria, which include Streptomyces, are dominant in arid environments [56], which explains why they are easily isolated from Greek soils.…”
Section: Discussionmentioning
confidence: 99%
“…The geomorphological and climate conditions prevailing in Greece, including its geographical position and its dry Mediterranean climate, result in soil reservoirs that have a high taxonomic and functional diversity of Streptomyces populations, providing a rich pool of strains with potential pharmaceutical value [9]. In addition to medicine, Greek strains have potential applications in the field of agriculture as biocontrol agents and growth promoters [9][10][11]. Each of these streptomycetes produces multiple secondary metabolites; for example, Streptomyces ambofaciens BI0048, an endophyte isolated from the red alga Laurencia glandulifera from Attiki, produced 10 different α-pyrone polyketides as well as benzoic acid, hydrocinnamic acid and (E)-cinnamic acid [12].…”
Section: Introductionmentioning
confidence: 99%
“…M. incognita second stages died at a higher rate when Streptomyces hydrogens was used, which resulted in a lower rate of egg hatching (Kaur et al, 2016). Meidani et al, 2020, found that culture supernatants, cell solvent extracts, and spore suspensions of Streptomyces strains from Greece have nematicidal action against M. incognita and M. javanica, as well as negative crop production consequences.…”
Section: Introductionmentioning
confidence: 99%